Peramalan Produksi Serundeng Kentang dengan Fuzzy Tsukamoto - Eka Praja Wiyata Mandala; Dewi Eka Putri (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Production is a very important process for a business that produces products. In a culinary business, for example, production is a determining factor so that the culinary products produced can be distributed to stores for sale. The culinary business is mostly done by small and medium businesses. One of them is UKM Yandi which a produces potato flakes as its culinary products. UKM Yandi distributes a potato flakes to 10 minimarkets in Padang every week. The problem that occurs is often the amount of production is greater than the demand of the minimarket while the remaining stock in the minimarket is still large, so there is often a buildup of products on the minimarket because it is not sold. This research provides a solution for UKM Yandi to forecast the production of potato flakes using the Fuzzy Tsukamoto approach, using input variables, the remaining stock at the minimarket in the previous week and the request submitted by the minimarket for the following week, while the output variable is the amount of production carried out by UKM Yandi. This research makes a web-based application that can be used by UKM Yandi owners to forecast the production of potato flakes, so they can be accessed from anywhere. The results of this research are able to help and facilitate UKM Yandi in forecasting the production of potato flakes because it produces a number with a certain number of packets to be produced